Sea Ice Monitoring by Remote Sensing - Sandven, Stein; Johannessen, Ola M. (The American Society for Photogrammetry & Remote Sensing, 2006)
Reprinted with permission from The American Society for Photogrammetry & Remote Sensing. Sandven, S. and O.M. Johannesen. “Sea Ice Monitoring by Remote Sensing.” Manual of Remote Sensing: Remote Sensing of the Marine Environment. James F.R. Gower, ed. 3rd Edtion, volume 6. Bethesda: American Society for Photogrammetry & Remote Sensing, 2006. 241-283. This article originally appeared as chapter 8 in the Manual of Remote Sensing, vol. 6, 3rd edition: Remote Sensing of the Marine Environment. The entire volume is available for purchase at www.asprs.org.